Efectos de procesamiento semántico en el desempeño lector de estudiantes universitarios novatos - Bargetto, Miguel Á. (2024)
Research in academic literacy has shown that scaffolding improves the reading of disciplinary texts. Included among the considered variables is the lexica. A robust vocabulary will result in better reading performance. To verify this, a semantic priming task and a reading comprehension test were applied to 31 first-year pedagogy students to establish whether there is a correlation between lexical processing and reading. The main findings indicate the establishment of weak semantic relations and normal reading performance. It is concluded that better reading performance is associated with slower lexical processing, which would suggest that readers engage in strategic operations to address comprehension tasks. This will allow for the formulation of scaffolding actions that highlight the importance of mastering the disciplinary vocabulary in order to safeguard an adequate reading task.